Genome-wide Association Study Identifies New Loci for Resistance to Sclerotinia Stem Rot in Brassica napus - Wu, Jian; Zhao, Qing; Liu, Sheng; Shahid, Muhammad; Lan, Lei; Cai, Guangqin; Zhang, Chunyu; Fan, Chuchuan; Wang, Youping; Zhou, Yongming (Frontiers in Plant Science, 2016)
Sclerotinia stem rot (SSR) caused by the necrotrophic fungus Sclerotinia sclerotiorum is a major disease in rapeseed (Brassica napus) worldwide. Breeding for SSR resistance in B. napus, as in other crops, relies only on germplasms with quantitative resistance genes. A better understanding of the genetic basis for SSR resistance in B. napus thus holds promise for the genetic improvement of disease resistance. In the present study, a genome-wide association study (GWAS) for SSR resistance in B. napus were performed using an association panel of 448 accessions genotyped with the Brassica 60K Infinium® single-nucleotide polymorphism (SNP) array. A total of 26 SNPs corresponding to 3 loci, DSRC4, DSRC6 and DSRC8 were associated with SSR resistance. Haplotype analysis showed that the 3 favourable alleles for SSR resistance exhibited cumulative effects. After aligning SSR resistance quantitative trait loci (QTL) identified in the present and previous studies to the B. napus reference genome, one locus (DSRC6) was found to be located within the conﬁdence interval of a QTL identiﬁed in previous QTL mapping studies and another two loci (DSRC4 and DSRC8) were considered novel loci for SSR resistance. A total of 39 candidate genes were predicted for the 3 loci based on the GWAS combining with the differentially expressed genes identified in previous transcriptomics analyses.